Identification of Volatile Metabolites from Five Fungal Species Cultivated on Two Media - Sunesson, A. (1995)
Five fungal species, Aspergillus versicolor, Penicillium commune, Cladosporium cladosporioides, Paecilomyces variotii, and Phialophora fastigiata, were cultivated on two media, malt extract agar and dichloran glycerol agar. Culture flasks provided with inlet and outlet tubes were used and purified, and humidified air was constantly led through the flasks. Air samples from the cultures were sorbed on Tenax GR and analyzed by thermal desorption-gas chromatography. The produced volatile metabolites were analyzed by mass spectrometry. Various hydrocarbons, alcohols, ketones, ethers, esters, sulfur-containing compounds, and terpenes were identified. The most commonly produced substances were 2-methyl-1-propanol, 2-methyl-1-butanol, 3-methyl-1-butanol, 3-methylfuran, and dimethyl disulfide. The production was highly dependent on both medium and species.